VERDA: A Multisampler Tool for Mesopelagic Nets - Castellón, Arturo; Olivar, M. Pilar (Journal of Marine Science and Engineering, 2023)
Special issue Technological Oceanography.-- 10 pages, 6 figures, 1 table.-- Data Availability Statement: No new data were created or analyzed in this study. Data sharing is not applicable to this article Different types and systems to discriminate plankton samples at different strata in the water column have been developed in recent decades. For sampling at sufficient depth, opening and closing zooplankton multinets are ideal because there is no contamination of one sample with organisms of the previous one. However, for bigger nets, such as those used to collect micronektonic organism, it is difficult to use multiple net units, and multiple cod ends are preferred because of their simplicity, but with the problem of sample contamination from having a common net passageway. We present here a cod-end Multisampler design, VERDA, that uses a carrousel-like system. Similar to some sediment traps, the system works like a revolver with six or eight compartments whose turning mechanism is triggered when the net arrives to a programmed depth level. This prototype was built with inexpensive and recycled components and electronics similar to Arduino® and Teensy PCB to carry out electronic control. The net we used for testing the equipment was a mid-size midwater trawl of ca. 30 m2 and total length of 58 m that works with a single towing cable and no doors. The overall system is useful for all type of ships, due to the relatively easy deployment operations and because the Multisampler does not need electrical cable or acoustics. In our case, we used a Marport® (Reykjavik Iceland) and Scanmar (Åsgårdstrand, Norway) sensors for real-time depth monitoring and opening distance This research was funded by the projects “Migrants and Active Flux in the Atlantic Ocean” (MAFIA, CTM2012-39587-C04) and “Biomass and Active Flux in the Bathypelagic Zone” (Bathypelagic, CTM2016-78853-R) from the Spanish Ministry of Economy and Competitiveness, and SUMMER (grant agreement number 817806) from the European Union (Horizon 2020 Research ...